Fibroblasts Drive Metabolic Reprogramming in Pacemaker Cardiomyocytes. Issue 1 (25th May 2022) - Chou, Pei-Chun; Liu, Chih-Min; Weng, Ching-Hui; Yang, Kai-Chien; Cheng, Mei-Ling; Lin, Yuh-Charn; Yang, Ruey-Bing; Shyu, Bai-Chuang; Shyue, Song-Kun; Liu, Jin-Dian; Chen, Shih-Pin; Hsiao, Michael; et al.
Abstract : Background: The sino atrial node (SAN) is characterized by the microenvironment of pacemaker cardiomyocytes (PCs) encased with fibroblasts. An altered microenvironment leads to rhythm failure. Operable cell or tissue models are either generally lacking or difficult to handle. The biological process behind the milieu of SANs to evoke pacemaker rhythm is unknown. We explored how fibroblasts interact with PCs and regulate metabolic reprogramming and rhythmic activity in the SAN. Methods: Tbx18 (T-box transcription factor 18)-induced PCs and fibroblasts were used for cocultures and engineered tissues, which were used as the in vitro models to explore how fibroblasts regulate the functional integrity of SANs. RNA-sequencing, metabolomics, and cellular and molecular techniques were applied to characterize the molecular signals underlying metabolic reprogramming and identify its critical regulators. These pathways were further validated in vivo in rodents and induced human pluripotent stem cell-derived cardiomyocytes. Results: We observed that rhythmicity in Tbx18-induced PCs was regulated by aerobic glycolysis. Fibroblasts critically activated metabolic reprogramming and aerobic glycolysis within PCs, and, therefore, regulated pacemaker activity in PCs. The metabolic reprogramming was attributed to the exclusive induction of Aldoc (aldolase c) within PCs after fibroblast-PC integration. Fibroblasts activated the integrin-dependent mitogen-activated protein kinase-E2F1 signal through cell-cell contact and turned on Aldoc expression in PCs. Interruption of fibroblast-PC interaction or Aldoc knockdown nullified electrical activity. Engineered Tbx18-PC tissue sheets were generated to recapitulate the microenvironment within SANs. Aldoc-driven rhythmic machinery could be replicated within tissue sheets. Similar machinery was faithfully validated in de novo PCs of adult mice and rats, and in human PCs derived from induced pluripotent stem cells. Conclusions: Fibroblasts drive Aldoc-mediated metabolic reprogramming and rhythmic regulation in SANs. This work details the cellular machinery behind the complex milieu of vertebrate SANs and opens a new direction for future therapy.